Extending Sensing Range by Physics Constraints in Multiband-Multiline Absorption Spectroscopy for Flame Measurement - Tengfei Jiao; Sheng Kou; Liuhao Ma; Kin-Pang Cheong; Wei Ren (Sensors)
The present numerical study proposes a technique to extend the sensing range of tunable diode laser absorption spectroscopy (TDLAS) for flame measurement by involving physics constraints on both gas condition and spectroscopic parameters in the interpretation of spectra from multiple bands. A total of 24 major spectral lines for 2 spectral segments 4029–4031 cm−1 and 7185–7186 cm−1 are determined by specially designed detection function and contribution filtering. Numerical tests on uniform and complicated combustion fields prove the high accuracy, strong robustness to noise, wide sensing range, and good compatibility with tomography. The present study provides a strong technique for future complex combustion detection with advanced laser sources of broad spectrum.